2006
DOI: 10.1295/polymj.pj2006004
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fully Aromatic Polysilarylenesiloxanes by Melt Polycondensation and Their Thermal Properties

Abstract: ABSTRACT:The melt polycondensation of the two kinds of the bis(hydroxydiphenylsilyl)arylene monomers, 1,4-bis(hydroxydiphenylsilyl)benzene and 4,4 0 -bis(hydroxydiphenylsilyl)biphenyl, was investigated. The thermal properties of the obtained polymers were studied by using a thermogravimetry analysis, a differential scanning calorimetry and a thermomechanical analysis. The IR spectra and the XRD patterns of the polymers indicated that the melt polycondensation occurred in the temperature range from 290 C to 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“… and showed 529ºC and 523ºC of  d5 , respectively, and did excellent thermal stability similar to the fully aromatic polysilarylenesiloxanes in our previous [6,7]. Although  had experienced unexpected large weight loss during the meltpolycondensation, the TG curve of obtained  almost coincided with that of .…”
Section: Solubility Of Polymerssupporting
confidence: 55%
See 2 more Smart Citations
“… and showed 529ºC and 523ºC of  d5 , respectively, and did excellent thermal stability similar to the fully aromatic polysilarylenesiloxanes in our previous [6,7]. Although  had experienced unexpected large weight loss during the meltpolycondensation, the TG curve of obtained  almost coincided with that of .…”
Section: Solubility Of Polymerssupporting
confidence: 55%
“…If perfect condensa tion reaction of  proceeded, the weight loss ratio was 3.2%. We had reported that meltpolyconden sation of a disilanol monomer proceeded with generating volatile compounds arising from deg radation [7]. The volatile compounds generated during the meltpolycondensation were trapped to analyze them by means of GCMS.…”
Section: Polysilarylenesiloxane () Prepared By Meltpolycondensationmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be caused by the elimination of the volatile organosilicon compound, such as a triphenyl silanol, from the chain-end as described in our previous report. 27 It was shown that the molecular weight of the copolymers also affected on the weight residues. On the other hand, the weight residues of CP-e and polyMS's were much smaller than the theoretical values.…”
Section: Thermal Properties Of Copolymersmentioning
confidence: 99%
“…Silarylene-containing polymers, which exhibit a wide range of physical properties depending on their composition and structure, have received considerable academic and commercial interests over the past 30 years (11,12). One of the prominent properties of silarylene-containing polymers is their excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%